2023
DOI: 10.3390/pharmaceutics15030998
|View full text |Cite
|
Sign up to set email alerts
|

Nanosystems, Drug Molecule Functionalization and Intranasal Delivery: An Update on the Most Promising Strategies for Increasing the Therapeutic Efficacy of Antidepressant and Anxiolytic Drugs

Abstract: Depression and anxiety are high incidence and debilitating psychiatric disorders, usually treated by antidepressant or anxiolytic drug administration, respectively. Nevertheless, treatment is usually given through the oral route, but the low permeability of the blood–brain barrier reduces the amount of drug that will be able to reach it, thus consequently reducing the therapeutic efficacy. Which is why it is imperative to find new solutions to make these treatments more effective, safer, and faster. To overcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 82 publications
(169 reference statements)
0
7
0
Order By: Relevance
“…Several studies have reported that the intranasal route can be a good option as a nose to brain targeting approach for treating the depressive disorders. , Trigeminal and olfactory pathways have been considered to be merely the routes via which the brain is linked to the outside environment [ , ]. Drugs with limited oral bioavailability because of substantial metabolism have been studied using this route as a viable alternative. Additionally, the utilization of this nasal route of administration of medication allows the various therapeutics to avoid the first-pass effect.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that the intranasal route can be a good option as a nose to brain targeting approach for treating the depressive disorders. , Trigeminal and olfactory pathways have been considered to be merely the routes via which the brain is linked to the outside environment [ , ]. Drugs with limited oral bioavailability because of substantial metabolism have been studied using this route as a viable alternative. Additionally, the utilization of this nasal route of administration of medication allows the various therapeutics to avoid the first-pass effect.…”
Section: Discussionmentioning
confidence: 99%
“…The V1 and V2 branches of trigeminal nerve innervate the nasal cavity and transmit drug molecules to the brain stem both intracellularly and extracellularly [ 7 ]. Intranasal administration of the molecules allows them to penetrate brain tissue via the olfactory and trigeminal pathways bypassing the blood-brain-barrier (BBB) [ 25 , 26 ]. This is particularly important because the BBB is a very tight, selectively permeable membrane that helps maintain homeostasis in the CNS environment and protects the CNS from exposure to xenobiotics and toxic substances [ 13 , 14 , 27 ].…”
Section: The Nasal Cavity As a Promising Space For Drug Deliverymentioning
confidence: 99%
“…The intranasal administration of intravenous formulations of several drugs (fentanyl, sufentanil, ketamine, hydromorphone, midazolam, haloperidol, naloxone, glucagon) may be an effective alternative to intramuscular or intravenous administration [ 26 ]. In a paper by Lam et al (2020), it was stated that formulations available for intravenous delivery can be used for nasal administration using appropriate devices such as a mucosal atomization device (MAD) [ 2 ].…”
Section: Optimizing Intranasal Drug Deliverymentioning
confidence: 99%
See 2 more Smart Citations